Interfaces of Strategic Leaders: A Conceptual Framework, Review, and Research Agenda - Simsek, Zeki; Heavey, Ciaran; Fox, Brian Curtis (Journal of management, 2018)
Interfaces are of growing importance for theorizing and testing the influence of strategic leaders on firm behavior and actions. But despite their relevance and ubiquity, the lack of a commonly accepted definition and unifying framework has hindered researchers’ ability to take stock, synthesize, and systematize extant knowledge. We first develop an encompassing definition and organizing framework to review 122 prior studies across three decades. We then chart promising directions for future research around three concepts central to the framework and review: (1) Why do interfaces occur? (2) What happens at these interfaces? and (3) What are the impacts of interfaces? Together, the encompassing definition, framework, review, and specific directions for future research provide the much needed platform to agglutinate research and advance strategic leader interfaces as the next frontier of strategic leadership research.